Description of three new species of spider genus Leptonetela Kratochvíl, 1978 from caves of Hunan Province, China (Araneae, Leptonetidae) - He, Ailan; Liu, Jinxin; Xu, Xiang; Yin, Haiqiang; Peng, Xianjin (Zootaxa, 2019)
Three new species of the spider family Leptonetidae from caves in Hunan Province, China are described: Leptonetela biocellata sp. nov., Leptonetela latapicalis sp. nov. and Leptonetela tangi sp. nov. Detailed illustrations of the three new species are provided.